The Nobel Memorial laureates in economics : an introduction to their careers and main published works - Vane, Howard R.; Mulhearn, Chris (Cheltenham : Northhampton, MA : Edward Elgar Pub., 2005)
This reference describes the careers and main published works of each of the laureates since the prize for economics was established in 1969. The entries are presented in chronological order, and each is accompanied by a b&w photograph of the economist profiled.
Includes bibliographical references and index.
oif 03/02/15
Loan
Keywords: Economists -- Biography; Nobel Prize winners -- Biography; Economics -- History; Nobel Prizes -- History